Imbalance of the hemocoagulation and fibrinolysis systems under conditions of diabetes mellitus complicated by acute circulatory disturbance in the pool of carotid arteries of rats - Tkachuk, S.; Povar, M.; Gerush, N.; Tkachuk, O. (Journal of Education, Health and Sport, 2021)
Introduction. Both cerebral ischemia and diabetes mellitus (DM) are evidenced to be associated with hypercoagulation state, though today the facts concerning hemocoagulation condition with diabetes mellitus complicated by cerebral ischemia-reperfusion are lacking. The aim of the study. To examine the dynamics of interrelations between the pro-, anticoagulant and fibrinolytic parameters in rats with diabetes mellitus complicated by acute cerebral circulatory disturbance. Results. At the early ischemic-reperfusion period activation of the pro-coagulant potential (decrease of prothrombin and thrombin time and increase of fibrinogen content) is found to be balanced by a reduced activity of XIII factor and an increase activity of antithrombin III in rats without diabetes mellitus. At the same period in rats with diabetes increase of the pro-coagulant potential is accompanied by the activation of XIII factor and a reduced activity of antithrombin III promoting clot formation. On the 12th day of the observation the parameters of the coagulation chain in the hemostasis system and antithrombin III return to the level of the control animals in rats without diabetes, but in rats with diabetes the factors of intensification of a thrombotic risk remain activated. At the early and late ischemic-reperfusion periods the parameters of blood fibrinolytic activity increase in rats without diabetes; in animals with diabetes mellitus the parameters of fibrinolytic activity remain without changes at the early period of observation (except decrease of a potential plasminogen activity), and they decrease on the 12th day of the post-ischemic period, which deteriorates conditions of thrombolysis. Conclusions. Complication of diabetes mellitus by ischemic-reperfusion lesion of the brain results in imbalance in the hemocoagulation system at the expense of intensification of pro-coagulant mechanisms, and promotes inhibition of fibrinolytic processes with advanced changes in the dynamics of observation.